2020
DOI: 10.1148/radiol.2019190748
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade Rate of Percutaneously Diagnosed Pure Atypical Ductal Hyperplasia: Systematic Review and Meta-Analysis of 6458 Lesions

Abstract: Background: Management of percutaneously diagnosed pure atypical ductal hyperplasia (ADH) is an unresolved clinical issue.Purpose: To calculate the pooled upgrade rate of percutaneously diagnosed pure ADH. Materials and Methods:A search of MEDLINE and EMBASE databases was performed in October 2018. Preferred Reporting Items for Systematic Reviews and Meta-Analyses, or PRISMA, guidelines were followed. A fixed-or random-effects model was used, along with subgroup and meta-regression analyses. The Newcastle-Otta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 107 publications
6
55
0
Order By: Relevance
“…The upgrade rates for ADH are very variable, ranging between 7% and 45%. 4,[21][22][23][24] Some studies suggest ADH may be overtreated by open surgical excisional biopsy, 4,[23][24][25] thus new approaches have been made based on surveillance, especially if all microcalcifications are removed using VAEB or if co-existing columnar cell lesion is present. 23,26,27 Management of ADH may have implications for DCIS, as ADH is regarded as a precursor lesion to DCIS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upgrade rates for ADH are very variable, ranging between 7% and 45%. 4,[21][22][23][24] Some studies suggest ADH may be overtreated by open surgical excisional biopsy, 4,[23][24][25] thus new approaches have been made based on surveillance, especially if all microcalcifications are removed using VAEB or if co-existing columnar cell lesion is present. 23,26,27 Management of ADH may have implications for DCIS, as ADH is regarded as a precursor lesion to DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…4,[21][22][23][24] Some studies suggest ADH may be overtreated by open surgical excisional biopsy, 4,[23][24][25] thus new approaches have been made based on surveillance, especially if all microcalcifications are removed using VAEB or if co-existing columnar cell lesion is present. 23,26,27 Management of ADH may have implications for DCIS, as ADH is regarded as a precursor lesion to DCIS. 5,[21][22][23] To date, there are several large prospective randomized controlled trials investigating active surveillance for low-risk DCIS compared to conventional surgery with or without adjuvant radiotherapy or hormonal therapy: LOw Risk DCIS study (LORD, Europe), The LOw RISk DCIS trial (LORIS, UK) and Comparing an Operation to Monitoring, With or Without Endocrine Therapy (COMET, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagoner et al ( 25 ) observed an ADH upgrade rate of 5% (three of 57 cases) when percutaneous biopsy resulted in the complete retrieval of all suspicious calcifications followed by subsequent excision. Schiaffino et al ( 26 ) performed a meta-analysis study including 6458 lesions to estimate the upgrade rate of percutaneously diagnosed pure ADH and found that even if patients with apparent complete lesion removal after biopsy were considered, the pooled upgrade rate was 14%. Most studies emphasized the importance of pathological diagnosis of calcified lesions, but none of them mentioned the association between non-calcified lesions and disease ( 16 17 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the retrieved full-text articles were downloaded and read by our investigators for information extraction. Then, the Newcastle-Ottawa scale (25), a critical appraisal tool for studies in systematic review, was used to assess the quality of all the articles we included in this review. See Appendix E1 (supplement) for details on article inclusion and exclusion criteria.…”
Section: Decoding and Systematization Of Medical Imaging Featuresmentioning
confidence: 99%